2017
DOI: 10.25258/ijpqa.v8i03.9567
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Activity of Thujaoccidentalis,ThujaorientalisandChamaecyparisobtusa

Abstract: The antibacterial activity of three Cupressaceae plants (Thujaoccidentalis,ThujaorientalisandChamaecyparisobtusa) was tested against three bacteria using the agar diffusion method. The ether and ethylacetate fraction of crude methanol extract from the three plants showed potent antibacterial activity against the tested microorganisms. The result showed that Staphylococcus aureus revealed the most sensitivity among the tested bacteria. Thujaoccidentalisether fraction and Thujaorientalis hexane fraction exhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…Natural products and/or EOs having a MIC of 2 mg/mL or less may be deemed to have strong antimicrobial activity method [ 51 ]. Our findings are in agreement with those reported in the literature [ [52] , [53] , [54] , [55] ], which showed the efficacy of this EO as a potent antimicrobial agent at minimum concentrations (ranged between 31.25 and 125.0 μg/mL). However, the reported MICs and MBCs values are slightly different from some studies; it was demonstrated that MICs of TAEO varied from 12.5 to 25 μg/mL and their MBCs ranged from 25 to 50 μg/mL using the agar diffusion test assay [ 56 ].…”
Section: Resultssupporting
confidence: 93%
“…Natural products and/or EOs having a MIC of 2 mg/mL or less may be deemed to have strong antimicrobial activity method [ 51 ]. Our findings are in agreement with those reported in the literature [ [52] , [53] , [54] , [55] ], which showed the efficacy of this EO as a potent antimicrobial agent at minimum concentrations (ranged between 31.25 and 125.0 μg/mL). However, the reported MICs and MBCs values are slightly different from some studies; it was demonstrated that MICs of TAEO varied from 12.5 to 25 μg/mL and their MBCs ranged from 25 to 50 μg/mL using the agar diffusion test assay [ 56 ].…”
Section: Resultssupporting
confidence: 93%